ETNOMATEMATIKA BUDAYA JAWA : INOVASI PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR - Hendra Erik Rudyanto; Apri Kartika Sari HS; Dea Pratiwi (Jurnal Bidang Pendidikan Dasar, 2019)
Abstract Innovation in learning mathematics needs to be done so that the learning objectives of mathematics can be achieved effectively. One of the innovations that can be done is to utilize Javanese cultural products in learning mathematics. Besides being able to learn mathematics well, students can also get to know their culture which is slowly being forgotten. This study aims to describe the results of ethnomatatics exploration of Javanese culture that can be utilized in mathematics learning. The research method used is qualitative, through exploratory studies with ethnographic approaches. In connection with this study, researchers tried to dig up informationthrough literature,observation (observation) and possible the existence of an interview process with several figures or Javanese community members who know information about the object to be excavated. Theresults of the study show that there are many Javanese cultural products that have the potential for learning mathematics such as cultural products in the form of artifacts, traditional foods, traditional games, batik, and so on. If the Javanese cultural product can be utilized in mathematics learning well, it will create meaningful learning for students. Abstrak Inovasi dalam pembelajaran matematika perlu dilakukan supaya tujuan belajar matematika dapattercapai secara efektif. Salah satu inovasi yang dapat dilakukan adalah memanfaatkan produkbudaya Jawa dalam pembelajaran matematika. Selain dapat belajar matematika dengan baik, siswajuga dapat mengenal budayanya yang lambat laun mulai terlupakan. Penelitian ini bertujuanmendeskripsikan hasil eksplorasi etnomatematika budaya Jawa yang dapat dimanfaatkan dalampembelajaran matematika. Metode penelitian yang digunakan yaitu kualitatif, melalui studieksplorasi dengan pendekatan etnografi. Sehubungan dengan penelitian ini, peneliti berusahamenggali informasi melalui kepustakaan, pengamatan (observasi) serta dimungkinkan adanyaproses wawancara dengan beberapa tokoh atau warga masyarakat Jawa yang mengetahuiinformasi mengenai objek yang akan digaliHasil penelitian menunjukkan bahwa banyak sekaliproduk-produk budaya Jawa yang berpotensi untuk pembelajaran matematika misalnya produkbudaya yang berupa artefak, makanan tradisional, permainan tradisional, batik, dan lainsebagainya. Jika produk budaya Jawa tersebut dapat dimanfaatkan dalam pembelajaranmatematika dengan baik, maka akan menciptakan pembelajaran yang bermakna bagi siswa.